Intelligent Active Force Control Applied To Precise Machine - Muhammad Hatifi, Mansor (2010)

(untitled)
This paper present about the performance of vibration control via active force control (AFC) scheme is investigated through simulation study by application of MATLAB/ Simulink® software. AFC is a widely used control scheme in dynamic system control, and it is a highly robust control scheme although under unknown disturbances and operation condition. In this study, the AFC is incorporated with conventional proportional-integral-derivative (PID) controller to control active vibration isolation system which is two degree of freedom (TDOF) cutting tool of turning machine model. A harmonic force due to unbalance rotating mass and a sinusoidal response that pretended to be an internal disturbances are applied into both axes of models(X and Y) respectively. Generally, the estimated mass (EM) is the most significant parameter in the AFC scheme, thus the interest in this study is to obtain the EM via conventional crude approximation method and intelligent fuzzy logic method. A new AFC scheme proposed in this study is named AFCFLC scheme which mean AFC co-operate with PID and FLC. The main purpose of this scheme is to obtain the optimum EM value via the intelligent method and to suppress vibration. Finally, a demonstration of comparison study between each control schemes is carried out and it is clearly shows that the proposed AFCFLC scheme is the most superior control method for both axes vibration isolation cutting tool models.